2020
DOI: 10.3390/buildings10060101
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study Involving Effect of Curing Regime on Elastic Modulus of Geopolymer Concrete

Abstract: Geopolymer Concrete (GPC) as a cement-less construction material has attracted worldwide attention due to its lower carbon footprint. There are numerous studies reported on GPC made using different by-products including fly-ash. However, since the use of bottom-ash is comparatively limited, making potassium-based GPC using this waste can be an alternative to Portland Cement Concrete (PCC). In this study, two methods of accelerated curing were used to determine the influence of elevated temperature on the compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 62 publications
(90 reference statements)
0
7
0
Order By: Relevance
“…where E is the modulus of elasticity (MPa), σ c is the compressive strength (MPa), and ρ is the unit weight (kg/m 3 ). Hence, as previously noted for mechanical strength, the stiffness properties of geocement-based compounds also depend on the composition (nature of raw materials and mixture), synthesis process, curing regime, and aggregate-GC ITZ [53]. Aboulayt et al [57] reported from their studies that adding FA in MK geopolymer grout reduces the reactivity of the mixtures, increases the packing density of the precursor powders, and promotes the retention of air bubbles in the matrix.…”
Section: Mechanical Propertiesmentioning
confidence: 81%
See 2 more Smart Citations
“…where E is the modulus of elasticity (MPa), σ c is the compressive strength (MPa), and ρ is the unit weight (kg/m 3 ). Hence, as previously noted for mechanical strength, the stiffness properties of geocement-based compounds also depend on the composition (nature of raw materials and mixture), synthesis process, curing regime, and aggregate-GC ITZ [53]. Aboulayt et al [57] reported from their studies that adding FA in MK geopolymer grout reduces the reactivity of the mixtures, increases the packing density of the precursor powders, and promotes the retention of air bubbles in the matrix.…”
Section: Mechanical Propertiesmentioning
confidence: 81%
“…In terms of technological applicability, the knowledge of this parameter is crucial to evaluate the stress and deformation distributions of a concrete element under a spatial stress state. High compressive strength and stiffness are the fundamental conditions for a civil structure to support high loads and avoid failure of serviceability [53,54]. On the other hand, high mechanical deformability results in a better impact on vibro-acoustic damping and sound insulation performance against impact noise [55].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The unique manufacturing process of these GC pavers includes using fly-ash and bottom ash, collected from waste produced in thermal power plants, then mixing it with sodium, Na-based polymers and curing at a higher temperature to attain strength and desired durability. The detailed process of producing GC pavers as well as their utility in real-applications can be found in [20][21][22]. Based on these findings [20][21][22], trial batches of Na-based Geopolymer concrete paver blocks (with mold of 150 × 150 × 100 mm) were manufactured and cured at 80 • C, at Lovely Professional University, India.…”
Section: Methodsmentioning
confidence: 99%
“…The detailed process of producing GC pavers as well as their utility in real-applications can be found in [20][21][22]. Based on these findings [20][21][22], trial batches of Na-based Geopolymer concrete paver blocks (with mold of 150 × 150 × 100 mm) were manufactured and cured at 80 • C, at Lovely Professional University, India. The strong and durable pavers obtained from the lab allowed the researchers to purchase 400 fly-ash based paver blocks casted in a commercial facility.…”
Section: Methodsmentioning
confidence: 99%